Lipoid proteinosis: Report of four siblings and brief review of the literature - Nanda, A.; Alsaleh, Q.A.; Al-Sabah, H.; Ali, A.M.A.; Anim, J.T. (Pediatric Dermatology, 2001)
Lipoid proteinosis (Urbach-Wiethe disease) is a rare autosomal recessive disorder associated with deposition of periodic acid-Schiff (PAS)-positive hyaline material in various tissues including skin, mucous membranes, and internal organs. A family is reported in which four siblings (two boys and two girls) born to nonconsanguineous parents had lipoid proteinosis. All had the characteristic hoarseness of voice and three had skin lesions. The diagnosis was confirmed by the presence of typical features on light and electron microscopy.
Keywords: case report; lipoid proteinosis